Inhibitory regulation of constitutive transient receptor potential-like cation channels in rabbit ear artery myocytes - Albert, A P (Blackwell Science Inc, 2004)
In the present study we have investigated an inhibitory pathway regulating a constitutively active Ca(2+)-permeable non-selective cation conductance (I(cat)) in rabbit ear artery smooth muscle cells. Constitutive single channel activity of I(cat) was recorded in cell-attached and inside-out patches with similar unitary conductance values. In inside-out patches with relatively high constitutive activity the G-protein activator GTPγS inhibited channel activity which was reversed by the protein kinase C (PKC) inhibitor chelerythrine indicating a G-protein pathway inhibits channel activity via PKC. Spontaneous channel activity was also suppressed by the G-protein inhibitor GDPβS suggesting a G-protein is also involved in initiation of constitutive channel activity. Bath application of antibodies to G(αq)/G(α11) enhanced channel activity whereas anti-G(α1−3)/G(αo) antibodies decreased basal channel activity which suggests that G(αq)/G(α11) and G(αι)/G(αo) proteins initiate, respectively, the inhibitory and excitatory cascades. The phospholipase C (PLC) inhibitor U73122 increased spontaneous activity which implies a role for PLC in the inhibitory pathway. Bath application of the diacylycerol (DAG) analogue 1-oeoyl-2-acetyl-sn-glycerol (OAG) decreased the probability of channel opening (NP(o)) and this was reversed by chelerythrine. Application of the PKC activator phorbol 12, 13-dibutyrate (PDBu) and chelerythrine, respectively, decreased and increased NP(o). These data indicate that spontaneously active cation channels are inhibited by a tonic inhibitory pathway involving G(αq)/G(α11)-mediated stimulation of PLC to generate DAG which activates PKC to inhibit channel opening. There were some patches with relatively low NP(o) and it was evident that the inhibitory pathway was particularly marked in these cases. Moreover in the latter patches GTPγS and OAG caused marked increases in NP(o). Together with inhibitory effects of GDPβS and anti-G(α1−3)/G(αo) antibodies the results suggest that there is constitutive G(αi)/G(αo) protein activity leading to channel opening via a DAG-mediated but PKC-independent mechanism. Finally, with whole-cell recording it is shown that noradrenaline increases I(cat) and the noradrenaline-evoked response is markedly potentiated by PKC inhibition. This latter observation shows that PKC also limits agonist-evoked I(cat) in these arterial myocytes.